(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Integrated agriculture system (Simantri) is one of the priority program in Bali Province in order to enhance agricultural sector’s role to support Bali Mandara. This paper aims to describe potency, opportunity, and support of the local governments to empower farmers through Simantri program. This program is initiated Bali Governor (2008-2013) and based on Prima Tani model. Simantri was initially started in 2009 in 10 sites of the Gapoktans’ demonstration plots in 7 regencies. Durineg the period of 2009-2013 Simantri developed into 400 sites out of 1,000 targeted sites in 2018 in 9 regencies/cities. Total budget spent by Bali Government Province for Simantri 2009-1013 was more than Rp 8 billion from social assistance and CSR funds. Simantri enhances relation among farm activities and utilizes farm wastes inside the groups. Simantri orients its activities based on agriculture without waste or zero waste and produces 4 F (Food, Feed, Fertilizer and Fuel). Livestock-farm integration implemented by Simantri boosts farmers’ group business, job opportunity, and supplies of food, feed, fertilizer, organic pesticide, and bio gas to meet group members’ demand and for commercial purpose supported by local governments. In the future it is expected that Simantri becomes an integrated agriculture-energy program for food self-reliance and farmers’ welfare. It is as also expected that this program sustains regardless the changes in local government leaders and all attached policies.